Computational study of the neutron flux produced by the 2H(d,n)3He reaction - Marangouli, G.; Kokkoris, M.; Lagoyannis, A.; Patronis, N.; Vlastou, R.; Diakaki, M. (HNPS Advances in Nuclear Physics, 2019)
Quasi-monoenergetic neutron beams, in the energy range of 4-10 MeV produced via the 2H(d,n)3He reaction, have been used for cross section measurements at the 5.5 MeV tandem T11/25 Accelerator Laboratory of NCSR “Demokritos”. For accurate cross section measurements, it is important that the energy profile of the neutron beam and the experimental conditions are well characterized. Therefore, an investigation of the energy dependence of the neutron fluence, especially taking into account the deuteron break up phenomenon, has been carried out in the present work, using the recently developed analytical and Monte-Carlo simulation code NeusDesc. Fission experimental data from 238U ultra-thin targets, were used to validate the simulated results. The fission fragments of the 238U(n,f) reaction have been detected via MicroMegas detectors and using the well known cross section of the 238U isotope, the neutron flux has been deduced. The simulated reaction rates were in good aggrement with the experiment ones, thus confirming the validity of the simulations.